Sealant for liquid crystal dropping process and method for manufacturing liquid crystal display panel
By using specific types of epoxy compounds and (meth)acrylic compounds in the sealant of the liquid crystal display panel, combining the heat curing agent and the photopolymerization initiator, the lack of bonding strength of the existing sealant in the narrow frame design is solved. The problem of this achieves high bonding strength and inefficient dissolving in liquid crystal.
Patent Information
- Application Number
- CN202180011036.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-03-02
- Filing Date
- 2021-02-24
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2041-02-24
AI Technical Summary
During the manufacturing process of the liquid crystal display panel, when the existing sealant is added drippingly in the uncured state, impurities and low molecular components are easily dissolution, resulting in poor display problems, and when narrow frames are realized, the bonding strength is insufficient , liquid crystal leakage and peeling problems are prone to occur.
Sealing is adopted which includes an epoxy compound containing a polymerizable functional group other than an epoxy group, a compound having a (meth)acrylic group and an epoxy group, a (meth)acrylic compound, a heat curing agent and a photopolymerization initiator. The content of the agent and epoxy compound is controlled at 22 to 38 mass %, so as to ensure high bonding strength of the sealing member and its characteristics that are not easily dissolved in the liquid crystal.
It realizes high bonding strength between the sealing members and the substrate in the liquid crystal display panel, avoids liquid crystal leakage and poor display problems, and supports narrow frame design to ensure product stability and performance.
Smart Images

Figure BDA0003764681030000281
Abstract
Description
Technical Field
[0001] The invention relates to a sealing agent for a liquid crystal dropping process and a method for manufacturing a liquid crystal display panel. Background Art
[0002] In the case of manufacturing a liquid crystal display panel using a liquid crystal drop process, a liquid crystal sealant is applied to form a seal pattern. Then, liquid crystal is dripped onto a substrate on which a seal pattern is formed, or onto a substrate paired therewith, and bonded in a vacuum. Thereafter, the seal pattern is cured by UV irradiation or heating to form a sealing member. However, in this method, since liquid crystal is dripped in an uncured state of the liquid crystal sealant, impurities and low molecular components in the liquid crystal sealant are sometimes dissolved into the liquid crystal. Moreover, if low molecular components and the like are dissolved into the liquid crystal, it is easy to produce a poor display called an afterimage in the liquid crystal display panel.
[0003] Here, the conventional liquid crystal sealant contains a UV-curable (meth) acrylic compound and a heat-curable epoxy compound. Moreover, epoxy compounds are usually not cured by UV curing. Therefore, a large amount of low molecular weight epoxy compounds are still contained in the seal pattern after UV curing. Moreover, if the seal pattern is heated for heat curing, the liquid crystal undergoes a phase transition due to heat, and the epoxy compound in the seal pattern is easily dissolved into the liquid crystal.
[0004] Therefore, the following scheme has been proposed: by using a compound having a (meth) acrylic group and an epoxy group in one molecule, UV curability and heat curability are ensured, and the dissolution of the epoxy compound into the liquid crystal is suppressed (for example, Patent Document 1). In addition, the following scheme has been proposed: by using a crystalline epoxy compound with a melting point of 50° C. or more, the dissolution of the epoxy compound into the liquid crystal is suppressed (Patent Document 2).
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2015-28184
[0008] Patent Document 2: Japanese Patent Application Publication No. 2006-23583 Summary of the invention
[0009] Problems to be solved by the invention
[0010] Here, in recent years, it is required to increase the liquid crystal display area of the liquid crystal display panel and narrow the width of the area surrounding it (hereinafter also referred to as "narrow frame"). For the realization of narrow frame, it is also indispensable to make the width of the sealing member thin. However, in the previous sealing member, if the width is made thin, the bonding strength is likely to become insufficient, peeling occurs at the interface between the substrate and the sealing member, and liquid crystal seepage is likely to occur.
[0011] In addition, the epoxy group contained in the epoxy compound etc. greatly contributes to the bonding strength between the sealing member and the substrate. In the technology described in the above-mentioned patent document 1, the compound having the epoxy group is polymerized by UV curing. Therefore, during thermal curing, the epoxy group is difficult to move freely, and the epoxy group cannot fully contribute to the bonding with the substrate. On the other hand, in the technology described in patent document 2, since the viscosity of the liquid crystal sealant will rise, it is difficult to include a large amount of epoxy compounds with high melting points in the liquid crystal sealant. Therefore, it is also difficult to obtain sufficient bonding strength by this technology.
[0012] The present invention is made in view of the above-mentioned problems. Specifically, the purpose is to provide a sealing agent for a liquid crystal drop process and a method for manufacturing a liquid crystal display panel, wherein the sealing agent for a liquid crystal drop process can form a sealing member with high bonding strength to a substrate that can also cope with the narrow frame of a liquid crystal display panel and is not easily dissolved in liquid crystal.
[0013] Means for solving problems
[0014] The present invention provides the following sealing agent for a liquid crystal dropping method.
[0015] [1] A sealing agent for a liquid crystal dropping process, comprising an epoxy compound having no polymerizable functional group other than an epoxy group, a compound containing a (meth)acrylic group and an epoxy group having both a (meth)acrylic group and an epoxy group in one molecule, a (meth)acrylic compound having no epoxy group, a thermosetting agent, and a photopolymerization initiator, wherein the content of the epoxy compound is 22 to 38% by mass, and a residual DC value measured 30 seconds after a mixture obtained by heating the sealing agent for a liquid crystal dropping process and a liquid crystal in a mass ratio of 1:10 at 120°C for 1 hour, applying a voltage of 5 V for 1 second, and short-circuiting for 0.1 second is 200% or less relative to a residual DC value measured 30 seconds after a mixture obtained by heating only the liquid crystal at 120°C for 1 hour, applying a voltage of 5 V for 1 second, and short-circuiting for 0.1 second.
[0016] [2] The sealing agent for a liquid crystal dropping process as described in [1], wherein, for each component contained in the sealing agent for a liquid crystal dropping process, the above-mentioned components and liquid crystal are mixed in a mass ratio of 1:10, heated at 120°C for 1 hour, a voltage of 5 V is applied for 1 second and short-circuited for 0.1 second, and the residual DC value is measured 30 seconds later, and the above-mentioned residual DC value of 98% by mass or more of the components in the sealing agent for a liquid crystal dropping process is 300% or less relative to the residual DC value measured 30 seconds later after heating only the liquid crystal at 120°C for 1 hour, a voltage of 5 V is applied for 1 second and short-circuited for 0.1 second.
[0017] [3] The sealing agent for liquid crystal dropping methods according to [1] or [2], wherein the ratio of the component having a molecular weight of 500 or more in the epoxy compound is 25% by mass or more.
[0018] [4] A sealing agent for a liquid crystal dropping process as described in any one of [1] to [3], wherein the aforementioned thermosetting agent is one or more selected from the group consisting of an organic acid dihydrazide-based thermolatent curing agent, an imidazole-based thermolatent curing agent, an amine adduct-based thermolatent curing agent, and a polyamine-based thermolatent curing agent.
[0019] [5] The sealing agent for liquid crystal dropping methods according to any one of [1] to [4], further comprising inorganic particles.
[0020] [6] The sealing agent for liquid crystal dropping methods according to any one of [1] to [5], further comprising organic particles.
[0021] [7] The sealing agent for a liquid crystal dropping method according to any one of [1] to [6], further comprising a silane coupling agent.
[0022] [8] A method for manufacturing a liquid crystal display panel, comprising: a step of coating a sealant for a liquid crystal dropping process described in any one of [1] to [7] on one of a pair of substrates to form a seal pattern; a step of dropping liquid crystal into a region of the seal pattern of the one substrate or onto the other substrate while the seal pattern is uncured; a step of overlapping the one substrate with the other substrate via the seal pattern; and a step of curing the seal pattern.
[0023] [9] The method for manufacturing a liquid crystal display panel according to [8], wherein in the step of curing the seal pattern, the seal pattern is irradiated with light.
[0024]
[10] The method for manufacturing a liquid crystal display panel according to [9], wherein, in the step of curing the seal pattern, heating is performed after irradiating with light.
[0025] Effects of the Invention
[0026] The sealing agent for liquid crystal drop process of the present invention is not easily dissolved in liquid crystal. Furthermore, the sealing member obtained by the sealing agent for liquid crystal drop process has high bonding strength with the substrate. Therefore, in the obtained liquid crystal display panel, liquid crystal leakage and afterimage are not easily generated, and narrow frame can be achieved. DETAILED DESCRIPTION
[0027] 1. Sealant for liquid crystal dropping process
[0028] The sealant for liquid crystal drop process of the present invention (hereinafter, also referred to as "sealant") is a member for making a sealing member of a liquid crystal display panel, and can be suitably used when a liquid crystal display panel is made by a liquid crystal drop process. However, it can also be used to make a liquid crystal display panel by a liquid crystal injection process, etc.
[0029] As mentioned above, in the conventional sealant, if a large amount of epoxy compounds that can help improve the bonding strength are included, there is a problem that the liquid crystal is easily contaminated when manufacturing the liquid crystal display panel. On the other hand, if the amount of epoxy compounds is reduced, there is a situation in which, for example, when the frame of the liquid crystal display panel is narrowed, sufficient bonding strength cannot be obtained, and peeling occurs between the substrate and the cured product of the sealant (sealing member).
[0030] In contrast, the inventors of the present application have conducted in-depth studies and found that by adjusting the composition of the sealant so that the amount of the epoxy compound is 22 to 38% by mass relative to the total amount of the sealant and the residual DC value of the mixture formed by mixing the sealant and the liquid crystal at a predetermined ratio is 200% or less relative to the residual DC value of the liquid crystal alone, the bonding strength between the obtained sealing member and the substrate becomes very high, and on the other hand, afterimages caused by the dissolution of components in the sealant are less likely to occur.
[0031] Here, the residual DC value of a mixture containing a sealant and a liquid crystal can be measured as described below. First, a sealant and a liquid crystal (for example, MLC-7026, manufactured by Merck) are put into a vial at a mass ratio of 1:10 and mixed. Then, heat it at 120°C for 1 hour. Next, take out the mixture and inject it into a glass unit (for example, KSSZ-10 / B111M1NSS05, manufactured by EHC) in which an orientation film and a transparent electrode are pre-formed. Then, a voltage of 5V is applied to the obtained unit for 1 second and short-circuited for 0.1 second. Thereafter, the voltage remaining after 30 seconds (residual DC value) is measured using a 6254 measuring device (manufactured by Toyo Technica).
[0032] On the other hand, when measuring the residual DC value of only the liquid crystal, only the liquid crystal is put into a small bottle and mixed. Then, it is heated at 120°C for 1 hour. Next, the liquid crystal is taken out and injected into a glass unit (for example, KSSZ-10 / B111M1NSS05, manufactured by EHC) on which an orientation film and a transparent electrode are pre-formed. A voltage of 5V is applied to the obtained unit for 1 second and short-circuited for 0.1 second. Then, the voltage (residual DC value) remaining after 30 seconds is measured using, for example, a 6254 type measuring device (manufactured by Toyo Technica).
[0033] Here, the residual DC value of the mixture containing the sealant and the liquid crystal varies slightly depending on the type of liquid crystal, but it can be 200% or less relative to the residual DC value of the liquid crystal alone, and more preferably 180% or less. The residual DC value of the above mixture can be adjusted by the type of components constituting the sealant. For example, the residual DC value of the above mixture can be satisfied by adjusting the various components contained in the sealant so that the individual residual DC values are 300% or less relative to the residual DC value of the liquid crystal alone. More specifically, relative to the total amount of the sealant, it is preferred that the proportion of the components whose individual residual DC values are 300% or less relative to the residual DC value of the liquid crystal alone is 98% by mass or more.
[0034] The individual residual DC values of each component in the sealant can be measured as described below. First, each component and liquid crystal (for example, MLC-7026, manufactured by Merck) are put into a vial at a mass ratio of 1:10 and mixed. The mixture is heated at 120°C for 1 hour. Then, the mixture is injected into a glass unit (for example, KSSZ-10 / B111M1NSS05, manufactured by EHC) in which an orientation film and a transparent electrode are pre-formed. A voltage of 5V is applied to the resulting unit for 1 second and short-circuited for 0.1 seconds. Then, the voltage (residual DC value) remaining after 30 seconds is measured using, for example, a 6254 type measuring device (manufactured by Toyo Technica). It should be noted that the more preferred residual DC value of each component is less than 280% relative to the residual DC value of the blank liquid crystal.
[0035] Here, the sealant of the present invention comprises an epoxy compound, a compound containing a (meth) acrylic group and an epoxy group, a (meth) acrylic compound, a thermosetting agent, and a photopolymerization initiator. In addition to these components, inorganic particles, organic particles, a silane coupling agent, etc. may also be included as needed. It should be noted that the description of "(meth) acrylic-" in this specification includes "acrylic-" or "methacrylic-", or both of them.
[0036] Hereinafter, each component and physical properties of the sealant of the present invention will be described in detail.
[0037] (1) Epoxy compounds
[0038] Epoxy compounds are compounds that contain at least an epoxy group in one molecule and do not have polymerizable functional groups other than the epoxy group. The polymerizable functional group in this specification refers to a functional group that is activated by light irradiation or heating, a thermosetting agent, a photopolymerization initiator, a catalyst, etc. to undergo a polymerization reaction. The polymerizable functional group includes a photopolymerizable functional group, a thermally polymerizable functional group, an addition polymerization functional group, etc., and specific examples include a (meth) acrylic group, a vinyl group, an acrylamide group, an epoxy group, an isocyanate group, a silanol group, etc.
[0039] The number of epoxy groups contained in one molecule of the epoxy compound is preferably 2 or more. If the number of epoxy groups in the epoxy compound is 2 or more, the adhesion between the obtained sealing member and the substrate of the liquid crystal display panel becomes good. In addition, the moisture resistance of the obtained sealing member is also easily increased.
[0040] The epoxy compound may be in a liquid state or a solid state at room temperature. The softening point of the epoxy compound is preferably 40 to 110° C. from the viewpoint of the viscosity of the resulting sealant.
[0041] Here, the epoxy compound can be a monomer, an oligomer, or a polymer. The molecular weight (or weight average molecular weight) of the epoxy compound is generally preferably 220 to 3000, more preferably 250 to 2500, and further preferably 300 to 2000. Among them, relative to the total amount of the epoxy compound, the proportion of the component with a molecular weight of 500 or more is preferably 25% by mass or more. Epoxy compounds with a molecular weight of 500 or more are not easily soluble in liquid crystals. Therefore, for such epoxy compounds, the above-mentioned individual residual DC values are easily less than 300% compared to the residual DC value of the liquid crystal alone. The weight average molecular weight of the epoxy compound can be determined, for example, by gel permeation chromatography (GPC) (converted to polystyrene). Among them, the epoxy compound may also contain a part of the individual residual DC value relative to the residual DC value of the liquid crystal alone. Compounds that exceed 300%.
[0042] Here, the structure of the epoxy compound is not particularly limited, and examples thereof include aromatic epoxy compounds containing an aromatic ring in the main chain. Examples of aromatic epoxy compounds include: aromatic polyglycidyl ether compounds obtained by reacting aromatic diols represented by bisphenol A, bisphenol S, bisphenol F, bisphenol AD, etc., and diols modified with ethylene glycol, propylene glycol, and alkylene glycol, with epichlorohydrin; Novolac-type polyglycidyl ether compounds obtained by reacting polyphenols represented by Novolac resins derived from phenol, cresol, etc. and formaldehyde, polyalkenylphenols, or copolymers thereof, with epichlorohydrin; glycidyl ether compounds of xylylene phenol resins; naphthalene-type epoxy compounds; diphenyl ether-type epoxy compounds; biphenyl-type epoxy compounds; and the like.
[0043] More specifically, the aromatic epoxy compound is preferably a cresol Novolac epoxy compound, a phenol Novolac epoxy compound, a bisphenol A epoxy compound, a bisphenol F epoxy compound, a trisphenol methane epoxy compound, a trisphenol ethane epoxy compound, a trisphenol epoxy compound, a diphenyl ether epoxy compound, or a biphenyl epoxy compound.
[0044] The sealing agent may contain only one epoxy compound or two or more epoxy compounds. When the residual DC value of each epoxy compound is measured as described above, the value is preferably 150 mV or less.
[0045] In addition, the content of the epoxy compound is preferably 22 to 38% by mass, more preferably 22 to 36% by mass, and further preferably 23 to 35% by mass relative to the total amount of the sealant. If the amount of the epoxy compound is 25% by mass or more, the bonding strength between the sealing member obtained by the sealant and the substrate of the liquid crystal display panel increases, and the narrow frame of the liquid crystal display panel can also be coped with. On the other hand, if the amount of the epoxy compound is 38% by mass or less, it is easy to make the residual DC value of the mixture of the sealant and the liquid crystal measured as described above become less than 200% relative to the residual DC value of the liquid crystal alone, and it is not easy to produce afterimages in the obtained liquid crystal display panel.
[0046] (2) Compounds containing (meth)acrylic groups and epoxy groups
[0047] The (meth)acrylic group / epoxy group-containing compound may be a compound having an epoxy group and a (meth)acrylic group in one molecule.
[0048] When the sealant contains only the above-mentioned epoxy compound and the (meth) acrylic compound described later, their compatibility may be low. On the other hand, if the sealant further contains a compound containing a (meth) acrylic group and an epoxy group, the compatibility of the epoxy compound and the (meth) acrylic compound increases, and the epoxy compound is not easily eluted into the liquid crystal.
[0049] Here, the number of epoxy groups and (meth) acrylic groups contained in one molecule of the compound containing a (meth) acrylic group and epoxy group is not particularly limited, and for example, each may be 1. In addition, the number of epoxy groups and the number of (meth) acrylic groups may be the same or different. Examples of the compound containing a (meth) acrylic group and epoxy group include (meth) acrylic modified epoxy compounds obtained by reacting an epoxy compound with (meth) acrylic acid in the presence of a basic catalyst.
[0050] The epoxy compound used to prepare the (meth)acrylic modified epoxy compound is any epoxy compound having two or more epoxy groups in the molecule, including bisphenol-type epoxy compounds such as bisphenol A type, bisphenol F type, 2,2'-diallylbisphenol A type, bisphenol AD type, and hydrogenated bisphenol type; Novolac-type epoxy compounds such as phenol Novolac type, cresol Novolac type, biphenyl Novolac type, and trisphenol Novolac type; biphenyl-type epoxy compounds; naphthalene-type epoxy compounds, etc.
[0051] Among them, the crosslinking density of the (meth) acrylic modified epoxy compound obtained by (meth) acrylic modified trifunctional, tetrafunctional and other multifunctional epoxy compounds is high. Therefore, if the sealant contains such a (meth) acrylic modified epoxy compound, the bonding strength between the sealing member and the substrate is easily reduced when the liquid crystal display panel is manufactured. Therefore, the (meth) acrylic modified epoxy compound obtained by (meth) acrylic modified bifunctional epoxy compounds is preferred.
[0052] The epoxy compound used to prepare the (meth) acrylic modified epoxy compound is more preferably a biphenyl epoxy compound, a naphthalene epoxy compound, and a bisphenol epoxy compound. From the viewpoint of the coating efficiency of the sealant, it is further preferably a bisphenol epoxy compound such as bisphenol A and bisphenol F. It should be noted that the epoxy compound used to prepare the (meth) acrylic modified epoxy compound can be one or more than two. In addition, the epoxy compound used to prepare the (meth) acrylic modified epoxy compound is preferably highly purified by molecular distillation, washing method, etc.
[0053] In addition, the reaction of the above-mentioned epoxy compound and (meth) acrylic acid can be carried out according to conventional methods. If this reaction is carried out, (meth) acrylic acid reacts with a part of the epoxy groups in the epoxy compound to obtain a (meth) acrylic acid-modified epoxy compound having a (meth) acrylic acid group and an epoxy group. Among them, there is the following situation: in the reaction product, not only the (meth) acrylic acid-modified epoxy compound is contained, but also unreacted epoxy compounds, (meth) acrylic acid and (meth) acrylic acid The (meth) acrylic acid compound obtained by the reaction of all epoxy groups of the epoxy compound. It is also possible to separate only the (meth) acrylic acid-modified epoxy compound from the product and use it in a sealant, and the unreacted epoxy compound is equivalent to the above-mentioned epoxy compound that does not have a polymerizable functional group other than the epoxy group. In addition, the (meth) acrylic acid compound obtained by the reaction of all epoxy groups of the epoxy compound with (meth) acrylic acid is equivalent to the (meth) acrylic acid compound described later. Therefore, the reaction product can also be used directly in a sealant.
[0054] Here, the molecular weight (weight average molecular weight) of the compound containing a (meth) acrylic group and an epoxy group is preferably, for example, 310 to 1000, and more preferably 350 to 900. The weight average molecular weight Mw of the compound containing a (meth) acrylic group and an epoxy group can be measured, for example, by gel permeation chromatography (GPC) (in terms of polystyrene conversion). If the molecular weight of the compound containing a (meth) acrylic group and an epoxy group is within this range, the viscosity of the sealant is easily within the desired range.
[0055] Relative to the total amount of the sealant, the amount of the compound containing a (meth) acrylic group and an epoxy group contained in the sealant is preferably 15 to 50% by mass, more preferably 18 to 40% by mass, and further preferably 20 to 35% by mass. If the amount of the compound containing a (meth) acrylic group and an epoxy group is 15% or more by mass, the bonding strength between the sealing member obtained by the sealant and the substrate of the liquid crystal display panel is increased, and the narrow frame of the liquid crystal display panel can also be coped with. On the other hand, if the amount of the epoxy compound is 50% or less by mass, it is easy to make the residual DC value of the mixture of the sealant and the liquid crystal less than 200% relative to the residual DC value of the liquid crystal alone, and it is not easy to produce afterimages in the obtained liquid crystal display panel.
[0056] (3) (Meth) acrylic acid compounds
[0057] The (meth)acrylic compound is a compound containing one or more (meth)acrylic groups in one molecule and is a compound having no epoxy group. The (meth)acrylic compound may be a monomer, an oligomer, or a polymer.
[0058] The number of (meth)acrylic groups contained in one molecule of the (meth)acrylic compound is preferably 2 or more. When the number of (meth)acrylic groups in the (meth)acrylic compound is 2 or more, the photocurability of the sealant becomes good.
[0059] Here, examples of the (meth)acrylic compound include: di(meth)acrylates of polyethylene glycol, propylene glycol, polypropylene glycol, etc.; di(meth)acrylate of tris(2-hydroxyethyl)isocyanurate; di(meth)acrylate of a diol obtained by adding 4 or more ethylene oxide or propylene oxide to 1 mol of neopentyl glycol; di(meth)acrylate of a diol obtained by adding 2 mol of ethylene oxide or propylene oxide to 1 mol of bisphenol A; di- or tri(meth)acrylate of a triol obtained by adding 3 or more ethylene oxide or propylene oxide to 1 mol of trimethylolpropane; di(meth)acrylate of a diol obtained by adding 4 or more ethylene oxide or propylene oxide to 1 mol of bisphenol A; tri(meth)acrylate of tris(2-hydroxyethyl)isocyanurate; tri(meth)acrylate of tris(hydroxymethyl)propane; Propane tri(meth)acrylate, or its oligomer; pentaerythritol tri(meth)acrylate, or its oligomer; dipentaerythritol poly(meth)acrylate; isocyanuric acid tri(acryloxyethyl) ester; caprolactone-modified isocyanuric acid tri(acryloxyethyl) ester; caprolactone-modified isocyanuric acid tri(methacryloxyethyl) ester; alkyl-modified dipentaerythritol poly(meth)acrylate; caprolactone-modified dipentaerythritol poly(meth)acrylate; hydroxypivalic acid neopentyl glycol di(meth)acrylate; caprolactone-modified hydroxypivalic acid neopentyl glycol di(meth)acrylate; ethylene oxide-modified phosphoric acid (meth)acrylate; ethylene oxide-modified alkylated phosphoric acid (meth)acrylate; oligomeric (meth)acrylates of neopentyl glycol, trimethylolpropane, and pentaerythritol; and the like. Moreover, compounds obtained by reacting all of the above-mentioned epoxy compounds having two or more functional groups with (meth)acrylic acid are also included.
[0060] Among them, from the viewpoint of making it easy to make the elastic modulus of the film after photocuring of the sealant within the desired range, the glass transition temperature of the (meth)acrylic compound is preferably 25° C. or higher and lower than 200° C. The glass transition temperature is more preferably 40° C. to 200° C., and further preferably 50 to 150° C. The glass transition temperature can be measured using a viscoelasticity measuring device (DMS).
[0061] In addition, the molecular weight (or weight average molecular weight) of the (meth)acrylic compound is preferably 310 to 1000, and more preferably 400 to 900. The weight average molecular weight Mw of the (meth)acrylic compound can be measured by gel permeation chromatography (GPC), for example (in terms of polystyrene). If the molecular weight of the (meth)acrylic compound is within this range, the viscosity of the sealant is easily within the desired range.
[0062] The amount of the (meth)acrylic compound contained in the sealant depends on the desired curability of the sealant, but is preferably 15 to 40% by mass, more preferably 18 to 35% by mass, and further preferably 20 to 32% by mass relative to the total amount of the sealant. If the amount of the (meth)acrylic compound is within the above range, the elastic modulus of the sealant after photocuring tends to be good.
[0063] (4) Thermal curing agent
[0064] The thermosetting agent is a component that can cure the above-mentioned epoxy compound by heating. Among them, the thermosetting agent is preferably the following compound: a compound that does not cure the above-mentioned epoxy compound and the compound containing a (meth) acrylic group and epoxy group under normal storage conditions (room temperature, visible light, etc.), but can cure these compounds by heating. According to the sealant containing such a thermosetting agent, storage stability and thermosetting properties can be achieved at the same time. In addition, as a thermosetting agent, a compound that can cure the epoxy compound (hereinafter also referred to as "epoxy curing agent") is preferred.
[0065] From the viewpoint of improving the viscosity stability of the sealant and not impairing the moisture resistance of the obtained sealing member, the melting point of the epoxy curing agent is preferably 50°C to 250°C, more preferably 100°C to 200°C, and further preferably 150°C to 200°C. If the melting point of the epoxy curing agent is within this range, the sealant can be one-liquid curable. If the sealant is one-liquid curable, it is not necessary to mix the main agent and the curing agent when using, so the workability is excellent.
[0066] Examples of the epoxy curing agent include organic acid dihydrazide-based thermal latent curing agents, imidazole-based thermal latent curing agents, amine adduct-based thermal latent curing agents, and polyamine-based thermal latent curing agents.
[0067] Examples of the epoxy curing agent include organic acid dihydrazide-based thermal latent curing agents, imidazole-based thermal latent curing agents, dicyandiamide-based thermal latent curing agents, amine adduct-based thermal latent curing agents, and polyamine-based thermal latent curing agents.
[0068] Examples of organic acid dihydrazide-based thermal latent curing agents include adipic acid dihydrazide (melting point 181° C.), 1,3-bis(hydrazinocarbonylethyl)-5-isopropylhydantoin (melting point 120° C.), 7,11-octadecadiene-1,18-dicarbohydrazide (melting point 160° C.), dodecanedioic acid dihydrazide (melting point 190° C.), and sebacic acid dihydrazide (melting point 189° C.).
[0069] Examples of the imidazole-based thermal latent curing agent include 2,4-diamino-6-[2′-ethylimidazolyl-(1′)]-ethyltriazine (melting point: 215 to 225° C.) and 2-phenylimidazole (melting point: 137 to 147° C.).
[0070] Examples of the dicyandiamide-based heat latent curing agent include dicyandiamide (melting point: 209° C.) and the like.
[0071] Amine adduct-based thermal latent curing agents are thermal latent curing agents formed of an addition compound obtained by reacting an amine-based compound having catalytic activity with an arbitrary compound. Examples of amine adduct-based thermal latent curing agents include Amicure PN-40 (melting point 110° C.) manufactured by Ajinomoto Fine-Techno Co., Inc., Amicure PN-23 (melting point 100° C.) manufactured by Ajinomoto Fine-Techno Co., Inc., Amicure PN-31 (melting point 115° C.) manufactured by Ajinomoto Fine-Techno Co., Inc., Amicure PN-H (melting point 115° C.) manufactured by Ajinomoto Fine-Techno Co., Inc., Amicure MY-24 (melting point 120° C.) manufactured by Ajinomoto Fine-Techno Co., Inc., and Amicure MY-H (melting point 131° C.) manufactured by Ajinomoto Fine-Techno Co., Inc.
[0072] The polyamine-based thermal latent curing agent is a thermal latent curing agent having a polymer structure obtained by reacting an amine with an epoxy, and examples thereof include Adeka Hardener EH4339S (softening point 120 to 130° C.) and Adeka Hardener EH4357S (softening point 73 to 83° C.) manufactured by Adeka Corporation.
[0073] Among the above, organic acid dihydrazide-based thermolatent curing agents, imidazole-based thermolatent curing agents, amine adduct-based thermolatent curing agents, or polyamine-based thermolatent curing agents are preferred from the viewpoints of availability, compatibility with other components, etc. The sealant may contain only one epoxy curing agent, or may contain two or more epoxy curing agents.
[0074] The content of the thermosetting agent is preferably 1 to 20 mass %, more preferably 2 to 18 mass %, and further preferably 3 to 15 mass % relative to the total amount of the sealant. When the amount of the thermosetting agent is within this range, the thermosetting property of the sealant becomes good.
[0075] (5) Photopolymerization initiator
[0076] The photopolymerization initiator may be any compound that generates active species upon exposure to light, and may be a self-cleaving type photopolymerization initiator or a hydrogen abstraction type photopolymerization initiator. The sealant may contain only one type of photopolymerization initiator or may contain two or more types of photopolymerization initiators.
[0077] Examples of the self-cleaving photopolymerization initiator include alkylphenone compounds (e.g., benzyl dimethyl ketal such as 2,2-dimethoxy-1,2-diphenylethane-1-one (IRGACURE 651 manufactured by BASF), α-aminoalkylphenone such as 2-methyl-2-morpholino(4-thiomethylphenyl)propane-1-one (IRGACURE 907 manufactured by BASF), 1-hydroxycyclohexylphenyl ketone (IRGACURE 651 manufactured by BASF), 184) etc.), acylphosphine oxide compounds (e.g. 2,4,6-trimethylbenzoin diphenylphosphine oxide), titanocene compounds (e.g. bis(η5-2,4-cyclopentadien-1-yl)-bis(2,6-difluoro-3-(1H-pyrrol-1-yl)-phenyl)titanium), acetophenone compounds (e.g. diethoxyacetophenone, 2-hydroxy-2-methyl-1-phenylpropane-1-one, benzyldimethyl ketal, 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropane-1-one, 4-(2-hydroxyethoxy)phenyl-(2-hydroxy-2-propyl)ketone, 1-hydroxycyclohexylphenylketone, 2-methyl-2-morpholino(4-thiomethylphenyl)propane-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone, etc.), benzoylformate compounds (e.g. methyl phenylglyoxylate (methyl phenyl glyoxyl ester), benzoin ether compounds (e.g. benzoin, benzoin methyl ether, benzoin isopropyl ether), and oxime ester compounds (e.g. 1,2-octanedione-1-[4-(phenylthio)-2-(O-benzoyl oxime)] (IRGACURE OXE01 manufactured by BASF), ethyl ketone-1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-1-(O-acetyl oxime) (IRGACURE OXE02 manufactured by BASF)).
[0078] Examples of hydrogen abstraction type photopolymerization initiators include benzophenone compounds (e.g., benzophenone, methyl o-benzoylbenzoate, 4-phenylbenzophenone, 4,4'-dichlorobenzophenone, hydroxybenzophenone, 4-benzoyl-4'-methyl-diphenyl sulfide, acrylated benzophenone, 3,3',4,4'-tetrakis(tert-butylperoxycarbonyl)benzophenone, 3,3'-dimethyl-4-methoxybenzophenone, etc.), thioxanthone compounds (e.g., thioxanthone, 2-chlorothioxanthone (manufactured by Tokyo Chemical Industry Co., Ltd.), 1-chloro-4-propoxythioxanthone, 1-chloro-4-ethoxythioxanthone (Speedcure CPTX manufactured by Lambson Limited), 2-isopropylxanthone (Speedcure ITX), 4-isopropylthioxanthone, 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone (DETX) (Speedcure DETX manufactured by Lambson Limited), 2,4-dichlorothioxanthone, anthraquinone compounds (for example, 2-methylanthraquinone, 2-ethylanthraquinone, 2-tert-butylanthraquinone, 1-chloroanthraquinone, 2-hydroxyanthraquinone (2-Hydroxyanthraquinone manufactured by Tokyo Chemical Industry Co., Ltd.), 2,6-dihydroxyanthraquinone (Anthraflavic Acid manufactured by Tokyo Chemical Industry Co., Ltd.), 2-hydroxymethylanthraquinone (2-(Hydroxymethyl)anthraquinone manufactured by Junsei Chemical Co., Ltd.), etc.), and benzil compounds.
[0079] The absorption wavelength of the photopolymerization initiator is not particularly limited, and for example, a photopolymerization initiator that absorbs light with a wavelength of 360 nm or more is preferred. Among them, a photopolymerization initiator that absorbs light in the visible light region is more preferred, a photopolymerization initiator that absorbs light with a wavelength of 360 to 780 nm is further preferred, and a photopolymerization initiator that absorbs light with a wavelength of 360 to 430 nm is particularly preferred.
[0080] Examples of the photopolymerization initiator that absorbs light having a wavelength of 360 nm or longer include alkylphenone compounds, acylphosphine oxide compounds, titanocene compounds, oxime ester compounds, thioxanthone compounds, and anthraquinone compounds, and oxime ester compounds are preferred.
[0081] The structure of the photopolymerization initiator can be determined by combining high performance liquid chromatography (HPLC) and liquid chromatography mass spectrometry (LC / MS) with NMR measurement or IR measurement.
[0082] The molecular weight of the photopolymerization initiator is preferably, for example, 200 to 5000. If the molecular weight is 200 or more, the photopolymerization initiator is not easily dissolved into the liquid crystal when the sealant contacts the liquid crystal. On the other hand, if the molecular weight is 5000 or less, the compatibility with the above-mentioned (meth) acrylic acid compounds and the like increases, and the curability of the sealant tends to become good. The molecular weight of the photopolymerization initiator is more preferably 230 to 3000, and further preferably 230 to 1500.
[0083] The molecular weight of the photopolymerization initiator can be determined as the “relative molecular mass” of the molecular structure of the main peak detected when analyzed by high performance liquid chromatography (HPLC).
[0084] Specifically, a sample solution is prepared by dissolving a photopolymerization initiator in THF (tetrahydrofuran), and a high performance liquid chromatography (HPLC) measurement is performed. Then, the area percentage of the detected peaks (the ratio of the area of each peak to the total area of all peaks) is calculated to confirm the presence or absence of a main peak. The so-called main peak refers to the peak with the highest intensity (the peak with the highest peak height) among all peaks detected at a characteristic detection wavelength (for example, 400nm for thioxanthone compounds) for each compound. The relative molecular mass corresponding to the peak vertex of the detected main peak can be measured using liquid chromatography mass spectrometry (LC / MS: Liquid Chromatography Mass Spectrometry).
[0085] The amount of the photopolymerization initiator is preferably 0.1 to 8% by mass, more preferably 0.5 to 5% by mass, and further preferably 1 to 3% by mass relative to the total amount of the sealant. If the amount of the photopolymerization initiator is 0.1% by mass or more, the photocurability of the sealant tends to be good. If the amount of the photopolymerization initiator is 8% by mass or less, the photopolymerization initiator is not easily eluted into the liquid crystal.
[0086] (6) Inorganic particles
[0087] The sealant may further contain inorganic particles as necessary. When the sealant contains inorganic particles, the viscosity of the sealant, the strength of the obtained sealing member, the linear expansion property, etc. tend to be improved.
[0088] Examples of materials of inorganic particles include calcium carbonate, magnesium carbonate, barium sulfate, magnesium sulfate, aluminum silicate, zirconium silicate, iron oxide, titanium oxide, titanium nitride, aluminum oxide (alumina), zinc oxide, silicon dioxide, potassium titanate, kaolin, talc, glass beads, sericite activated clay, bentonite, aluminum nitride, silicon nitride, etc. The sealant may contain only one inorganic particle or two or more inorganic particles. Among the above, the inorganic particles are preferably silicon dioxide or talc.
[0089] The shape of the inorganic particles may be fixed shapes such as spheres, plates, needles, etc., or may be irregular shapes. When the inorganic particles are spherical, the average primary particle size of the inorganic particles is preferably 1.5 μm or less, and the specific surface area is more preferably 0.5 to 20 m 2 The average primary particle size of the inorganic particles can be measured by the laser diffraction method described in JIS Z8825-1. The specific surface area of the inorganic particles can be measured by the BET method described in JIS Z8830.
[0090] The content of the inorganic particles is preferably 0.1 to 25% by mass, more preferably 3 to 20% by mass, and further preferably 5 to 18% by mass relative to the total amount of the sealant. If the content of the inorganic particles is 0.1% by mass or more, the moisture resistance of the obtained sealing member is easily increased, and if it is 25% by mass or less, the coating stability of the sealant is not easily impaired.
[0091] (7) Organic particles
[0092] The sealant may further contain organic particles as necessary. If the sealant contains organic particles, it is easy to adjust the elastic modulus of the sealant after photocuring.
[0093] Examples of organic particles include silicone particles, acrylic particles, styrene particles such as styrene-divinylbenzene copolymers, and polyolefin particles. The sealant may contain only one type of organic particles or two or more types of organic particles. The average primary particle size of the organic particles is preferably 0.05 to 13 μm, more preferably 0.1 to 10 μm, and even more preferably 0.1 to 8 μm.
[0094] In addition, the shape of the organic particles is not particularly limited, but is preferably spherical, and more preferably round. The so-called spherical refers to the ratio of the minimum value (b) of the diameter of each particle to the maximum value (a) b / a=0.9 to 1.0. The average primary particle size of the organic particles can be measured by microscopy, specifically, by image analysis of an electron microscope. In addition, the surface of the organic particles is preferably smooth. If the surface is smooth, the specific surface area is reduced, and the amount of organic particles that can be added to the sealant is increased.
[0095] The content of the organic particles is preferably 0.1 to 20 mass %, more preferably 1 to 15 mass %, and further preferably 3 to 12 mass % relative to the total amount of the sealant. If the amount of the organic particles is within this range, the elastic modulus of the sealant after photocuring can be easily adjusted to a desired range.
[0096] (8) Others
[0097] The sealant of the present invention may further contain additives such as a thermal free radical polymerization initiator, a coupling agent such as a silane coupling agent, an ion trapping agent, an ion exchanger, a leveling agent, a pigment, a dye, a sensitizer, a plasticizer, and a defoaming agent as required.
[0098] Examples of silane coupling agents include vinyl trimethoxysilane, γ-(meth)acryloxypropyl trimethoxysilane, γ-glycidoxypropyl trimethoxysilane, γ-glycidoxypropyl triethoxysilane, etc. Relative to the total amount of sealant, the amount of silane coupling agent is preferably 0.01 to 6% by mass, more preferably 0.1 to 5% by mass, and further preferably 0.5 to 3% by mass. If the content of the silane coupling agent is 0.01% by mass or more, the resulting sealing member is likely to have sufficient adhesion. Among them, silane coupling agents are mostly substances with high residual DC values. Therefore, the amount of silane coupling agent is preferably less than 6% by mass.
[0099] The sealant may further include a spacer for adjusting the gap between the liquid crystal display panels.
[0100] The total amount of other components is preferably 1 to 50% by mass relative to the total amount of the sealant. If the total amount of other components is 50% by mass or less, the viscosity of the sealant is unlikely to increase excessively, and the coating stability of the sealant is unlikely to be impaired.
[0101] (9) Physical properties of sealant
[0102] The viscosity of the sealant at 25°C and 2.5 rpm is preferably 200 to 450 Pa·s, more preferably 300 to 400 Pa·s. If the viscosity is within the above range, when a pair of substrates are superimposed with the sealant (seal pattern) interposed therebetween, the sealant is easily deformed in a manner that fills the gap between them. Therefore, the gap between a pair of substrates of the liquid crystal display panel can be appropriately controlled.
[0103] In addition, from the viewpoint of the coating property of the sealant, the thixotropic index (TI value) of the sealant is preferably 1.0 to 1.5, and more preferably 1.1 to 1.3. The TI value is a value obtained by applying the measured values of the sealant at room temperature (25°C) and 0.5 rpm to the following formula (1) using an E-type viscometer, with the viscosity of the sealant at 0.5 rpm being η1 and the viscosity of the sealant at 5 rpm being η2.
[0104] TI value = (viscosity η1 at 0.5 rpm (25°C)) / (viscosity η2 at 5 rpm (25°C))... (1)
[0105] The residual DC value measured by mixing the sealing agent and the liquid crystal as described above is preferably 100 mV or less. In this case, it is preferable to measure using MLC-7026 manufactured by Merck as the liquid crystal.
[0106] 2. LCD panel
[0107] The liquid crystal display panel of the present invention comprises a pair of substrates, a frame-shaped sealing member disposed between the substrates, and a liquid crystal filled between the pair of substrates and inside the frame-shaped sealing member. In the liquid crystal display panel, the sealing member is a solidified product of the aforementioned sealant. The sealing member obtained by the aforementioned sealant has a high bonding strength with the substrate, and even if the sealing member is thinned, liquid crystal leakage is not likely to occur. In addition, the sealant is not likely to contaminate the liquid crystal. Therefore, afterimages are not likely to occur when the liquid crystal display panel is used.
[0108] The pair of substrates (also referred to as "display substrate and counter substrate") are both transparent substrates. Examples of the material of the transparent substrate include glass, polycarbonate, polyethylene terephthalate, polyethersulfone, PMMA, and the like.
[0109] TFT, color filter, black matrix, etc. may be arranged in a matrix on the surface of the display substrate or the counter substrate. An alignment film may be further formed on the surface of the display substrate or the counter substrate. The alignment film may contain a known organic alignment agent, an inorganic alignment agent, etc. In addition, a known liquid crystal may be used.
[0110] The manufacturing method of a liquid crystal display panel generally includes a liquid crystal dropping process and a liquid crystal injection process, but the manufacturing method of a liquid crystal display panel of the present invention is preferably a liquid crystal dropping process.
[0111] The manufacturing method of a liquid crystal display panel based on a liquid crystal dropping process includes: 1) a sealing pattern forming process, coating the aforementioned sealant on a substrate to form a frame-shaped sealing pattern; 2) a liquid crystal dropping process, in which, when the sealing pattern is not solidified, liquid crystal is dropped into an area on one substrate and surrounded by the sealing pattern, or into an area on another substrate and surrounded by the sealing pattern when the other substrate is placed opposite to the one substrate; 3) a superimposing process, superimposing one substrate and the other substrate with the sealing pattern in between; and 4) a curing process, curing the sealing pattern.
[0112] 1) In the sealing pattern forming step, the aforementioned sealant is applied on a substrate. The method of applying the sealant is not particularly limited, and as long as it is a method such as screen printing, coating based on a dispenser, etc. that can form a sealing pattern with a desired thickness and width, there is no particular limitation, and it is the same as the known method of applying the sealant.
[0113] In addition, the shape of the seal pattern formed can be appropriately selected according to the purpose of the liquid crystal display panel, and the shape can be a shape that does not leak liquid crystal. For example, it can be made into a rectangular frame shape, but it is not limited to this shape. The line width of the seal pattern is preferably 0.2 to 1.0 mm, and more preferably 0.2 to 0.5 mm.
[0114] 2) In the liquid crystal dropping process, a pair of substrates are placed opposite each other in a state where the sealing pattern is not solidified. Here, the so-called unsolidified state of the sealing pattern refers to a state where the curing reaction of the sealant has not proceeded to the gel point. It should be noted that before the liquid crystal dropping process, in order to suppress the dissolution of the sealant into the liquid crystal, the sealing pattern can be semi-solidified by light irradiation or heating. In addition, the liquid crystal dropping method is the same as the known liquid crystal dropping method, and the liquid crystal can be dropped on a substrate with a sealing pattern formed, or on a substrate (another substrate) without a sealing pattern formed.
[0115] 3) In the superimposition step, one substrate and the other substrate are superimposed so as to face each other with the seal pattern interposed therebetween. At this time, the gap between the substrates is controlled so as to fall within a desired range.
[0116] 4) In the curing step, the seal pattern is cured. The curing method of the seal pattern is not particularly limited, and preferably, the seal pattern is temporarily cured by irradiation with light of a specified wavelength and then formally cured by heating. The seal pattern can be cured instantly by light irradiation, and the components in the sealant can be suppressed from dissolving in the liquid crystal.
[0117] The wavelength of the irradiated light can be appropriately selected according to the type of photopolymerization initiator, and ultraviolet light is preferred. In addition, although the light irradiation time also depends on the composition of the sealant, it is, for example, about 10 minutes. At this time, the amount of energy irradiated can be an amount of energy that can cure the (meth) acrylic compound or the compound containing a (meth) acrylic group and epoxy group.
[0118] After irradiation with light, the epoxy compound or the compound containing a (meth)acrylic group or epoxy group is cured by heating. The heating temperature depends on the composition of the sealant, but is, for example, 100 to 150° C., and the heating time is preferably about 2 hours.
[0119] Example
[0120] The present invention will be described in detail based on Examples, but the present invention is not limited to these Examples.
[0121] <Synthesis Example 1> Preparation of Photocurable Composition 1 (Preparation of Composition Containing Methacrylic Acid-Modified Epoxy Compound)
[0122] 160 g of liquid bisphenol F epoxy compound (EPICLON830-S, manufactured by DIC Corporation, epoxy equivalent 160 g / eq), 0.1 g of polymerization inhibitor (p-methoxyphenol), 0.2 g of catalyst (triethanolamine), and 43.0 g of methacrylic acid were placed in a flask, and dry air was introduced, and the reaction was carried out for 5 hours while stirring under reflux at 90°C. The obtained composition was washed 20 times with ultrapure water to obtain a composition containing a methacrylic acid-modified epoxy compound (composition 1 containing a photocurable compound). The composition of the obtained composition was identified by NMR, and the result was the following ratio: 25 mol% of epoxy compound with epoxy groups at both ends, 50 mol% of methacrylic acid-modified epoxy compound having epoxy groups and methacrylic acid groups at the ends, and 25 mol% of (meth)acrylic acid compounds modified by methacrylic acid groups at both ends. The obtained composition was separated in a column, and the values of the residual DC of each were determined by the method described later. The results are shown in Table 1.
[0123] <Synthesis Example 2> Preparation of Photocurable Composition 2 (Preparation of Composition Containing Acrylic-Modified Epoxy Compound)
[0124] 190 g of liquid bisphenol A epoxy compound (EPICLON850-S, manufactured by DIC Corporation, epoxy equivalent 190 g / eq), 0.1 g of polymerization inhibitor (p-methoxyphenol), 0.2 g of catalyst (triethanolamine), and 36.0 g of acrylic acid were put into a flask, and dry air was introduced. The mixture was reacted for 5 hours while being refluxed and stirred at 90°C. The obtained composition was washed 20 times with ultrapure water to obtain an acrylic modified epoxy composition (photocurable composition 2). The composition of the obtained composition was identified by NMR, and the result was the following ratio: 25 mol% of epoxy compound with epoxy groups at both ends, 50 mol% of (meth) acrylic compound with epoxy groups and acrylic groups at the ends, and 25 mol% of (meth) acrylic compound with acrylic groups modified at both ends. The obtained composition was separated in a column, and the values of the residual DC of each were determined by the method described later. The results are shown in Table 1.
[0125] [Example 1]
[0126] 400 parts by mass of the photocurable composition 1, 100 parts by mass of an epoxy compound (EP-4010S, manufactured by ADEKA (bisphenol A type, residual DC value = 64 mV)), 50 parts by mass of an epoxy compound (850-S, manufactured by DIC Corporation (bisphenol A type, residual DC value = 133 mV), 50 parts by mass of a (meth)acrylic compound (Ebecryl 3700, manufactured by Daicel Cytec Corporation (residual DC value = 52 mV)), 80 parts by mass of a (meth)acrylic compound (2CL, manufactured by Shin-Nakamura Chemical Co., Ltd. (residual DC value = 73 mV)), 50 parts by mass of a thermosetting agent (adipic acid dihydrazide, manufactured by Otsuka Chemical Co., Ltd. (residual DC value = 53 mV)), 20 parts by mass of a photopolymerization initiator (OXE-01, BASF Japan Co., Ltd. (residual DC value = 68mV)), 150 parts by mass of inorganic particles (silica particles: S-100, Nippon Catalyst Chemical Co., Ltd. (residual DC value = 51mV)), 90 parts by mass of organic particles (fine particle polymer F351, Aica Kogyo Co., Ltd. (residual DC value = 55mV)), and 10 parts by mass of silane coupling agent (KBM-403, Shin-Etsu Chemical Co., Ltd. (residual DC value = 431mV)) were mixed. Then, they were fully mixed with a three-roller to form a uniform liquid to obtain a sealant.
[0127] [Example 2]
[0128] Except having changed the photocurable composition 1 into the photocurable composition 2, it carried out similarly to Example 1, and prepared the sealing agent.
[0129] [Example 3]
[0130] 400 parts by mass of the photocurable composition 2, 50 parts by mass of an epoxy compound (EP-4010S, manufactured by ADEKA, bisphenol A type (residual DC value = 64 mV)), 50 parts by mass of an epoxy compound (Epikote 1004AF, manufactured by Mitsubishi Chemical Corporation, bisphenol A type (residual DC value = 57 mV)), 50 parts by mass of an epoxy compound (850-S, manufactured by DIC Corporation, bisphenol A type (residual DC value = 133 mV)), 50 parts by mass of a (meth)acrylic compound (Ebecryl 3700, Daicel Cytec (residual DC value = 52mV)), 80 parts by weight of (meth) acrylic compound (2CL, Shin-Nakamura Chemical Co., Ltd. (residual DC value = 73mV)), 50 parts by weight of thermosetting agent (adipic acid dihydrazide, Otsuka Chemical Co., Ltd. (residual DC value = 53mV)), 20 parts by weight of photopolymerization initiator (OXE-01, BASF (residual DC value = 68mV)), 150 parts by weight of inorganic particles (silica particles: S-100, Nippon Shokubai Chemical Co., Ltd. (residual DC value = 51mV)), 90 parts by weight of organic particles (fine particle polymer F351, Aica Kogyo Co., Ltd. (residual DC value = 55mV)), and 10 parts by weight of silane coupling agent (KBM-403, Shin-Etsu Chemical Co., Ltd. (residual DC value = 431mV)) were mixed. Then, these were fully mixed by three rolls to form a uniform liquid to obtain a sealant.
[0131] [Example 4]
[0132] 500 parts by mass of the photocurable composition 1, 80 parts by mass of an epoxy compound (EP-4010S, manufactured by ADEKA, bisphenol A type (residual DC value = 64 mV)), 50 parts by mass of an epoxy compound (Epikote 1004AF, manufactured by Mitsubishi Chemical Corporation, bisphenol A type (residual DC value = 57 mV)), 50 parts by mass of epoxy compound (850-S, DIC Corporation, bisphenol A type (residual DC value = 133 mV)), 40 parts by mass of (meth) acrylic compound (2CL, Shin-Nakamura Chemical Industry Co., Ltd. (residual DC value = 73 mV)), 50 parts by mass of thermosetting agent (adipic acid dihydrazide, Otsuka Chemical Co., Ltd. (residual DC value = 53 mV)), 20 parts by mass of photopolymerization initiator (OXE-01, BASF Corporation (residual DC value = 68 mV)), 130 parts by mass of inorganic particles (silica particles: S-100, Nippon Shokubai Chemical Co., Ltd. (residual DC value = 51 mV)), 70 parts by mass of organic particles (fine particle polymer F351, Aica Kogyo Co., Ltd. (residual DC value = 55 mV)), and 10 parts by mass of a silane coupling agent (KBM-403, manufactured by Shin-Etsu Chemical Co., Ltd. (residual DC value = 431 mV)) were mixed.
[0133] [Example 5]
[0134] 430 parts by weight of the photocurable composition 2, 150 parts by weight of an epoxy compound (EP-4010S, manufactured by ADEKA, bisphenol A type (residual DC value = 64 mV), 100 parts by weight of a (meth)acrylic compound (Ebecryl 3700, manufactured by DaicelCytec, bisphenol A type (residual DC value = 52 mV)), 40 parts by weight of a (meth)acrylic compound (2CL, manufactured by Shin-Nakamura Chemical Co., Ltd. (residual DC value = 73 mV)), 50 parts by weight of a thermosetting agent (adipic acid dihydrazide, manufactured by Otsuka Chemical Co., Ltd. (residual DC value = 53 mV)), 20 parts by weight of a photopolymerization initiator (OXE-01, manufactured by BASF (residual DC value = 68 mV)), 130 parts by weight of inorganic particles (silica particles: S-100, manufactured by Nippon Shokubai Chemical Co., Ltd. (residual DC value = 51 mV)), 70 parts by weight of organic particles (fine particle polymer F351, manufactured by Aica Kogyo Chemical Co., Ltd.) Co., Ltd. (residual DC value = 55 mV)), and 10 parts by mass of a silane coupling agent (KBM-403, Shin-Etsu Chemical Co., Ltd. (residual DC value = 431 mV)) were mixed. Then, these were fully mixed with a three-roller to form a uniform liquid, thereby obtaining a sealing agent.
[0135] [Example 6]
[0136] 600 parts by weight of the photocurable composition 1, 80 parts by weight of an epoxy compound (Epikote 1004AF, manufactured by Mitsubishi Chemical Corporation, bisphenol A type (residual DC value = 57 mV)), 30 parts by weight of an epoxy compound (850-S, manufactured by DIC Corporation, bisphenol A type (residual DC value = 133 mV), 50 parts by weight of a thermosetting agent (adipic acid dihydrazide, manufactured by Otsuka Chemical Co., Ltd. (residual DC value = 53 mV)), 20 parts by weight of a photopolymerization initiator (OXE-01, manufactured by BASF Corporation (residual DC value = 68 mV)), 130 parts by weight of inorganic particles (silica particles: S-100, manufactured by Nippon Shokubai Chemical Co., Ltd. (residual DC value = 51 mV)), 70 parts by weight of an organic particle (fine particle polymer F351, manufactured by Aica Kogyo Chemical Co., Ltd.) Co., Ltd. (residual DC value = 55 mV)), and 20 parts by mass of a silane coupling agent (KBM-403, Shin-Etsu Chemical Co., Ltd. (residual DC value = 431 mV)) were mixed. Then, these were fully mixed with a three-roller to form a uniform liquid, thereby obtaining a sealant.
[0137] [Example 7]
[0138] 500 parts by weight of the photocurable composition 1, 200 parts by weight of an epoxy compound (EP-4010S, manufactured by ADEKA, bisphenol A type (residual DC value = 64 mV)), 40 parts by weight of an epoxy compound (850-S, manufactured by DIC, bisphenol A type (residual DC value = 133 mV)), 50 parts by weight of a thermosetting agent (adipic acid dihydrazide, manufactured by Otsuka Chemical Co., Ltd. (residual DC value = 53 mV)), 20 parts by weight of a photopolymerization initiator (OXE-01, manufactured by BASF (residual DC value = 68 mV)), 130 parts by weight of inorganic particles (silica particles: S-100, manufactured by Nippon Shokubai Chemical Co., Ltd. (residual DC value = 51 mV)), 50 parts by weight of an organic particle (fine particle polymer F351, manufactured by Aica Kogyo Chemical Co., Ltd.) Co., Ltd. (residual DC value = 55 mV)), and 10 parts by mass of a silane coupling agent (KBM-403, Shin-Etsu Chemical Co., Ltd. (residual DC value = 431 mV)) were mixed. Then, these were fully mixed with a three-roller to form a uniform liquid, thereby obtaining a sealing agent.
[0139] [Comparative Example 1]
[0140] 400 parts by mass of the photocurable compound 2, 50 parts by mass of an epoxy compound (850-S, manufactured by DIC Corporation, bisphenol A type (residual DC value = 133 mV)), 100 parts by mass of an epoxy compound (Epogosey NPG, manufactured by Yokkaichi Kogyo Co., Ltd., 1,4-butanediol diglycidyl ether (residual DC value = 300 mV)), 50 parts by mass of a (meth)acrylic compound (Ebecryl 3700, manufactured by Daicel Cytec Co., Ltd. (residual DC value = 52 mV)), 80 parts by mass of a (meth)acrylic compound (2CL, manufactured by Shin-Nakamura Chemical Co., Ltd. (residual DC value = 73 mV)), 50 parts by mass of a thermosetting agent (adipic acid dihydrazide, manufactured by Otsuka Chemical Co., Ltd. (residual DC value = 53 mV)), 20 parts by mass of a photopolymerization initiator (OXE-01, BASF Japan Co., Ltd. (residual DC value = 68mV)), 150 parts by mass of inorganic particles (silica particles: S-100, Nippon Catalyst Chemical Co., Ltd. (residual DC value = 51mV)), 90 parts by mass of organic particles (fine particle polymer F351, Aica Kogyo Co., Ltd. (residual DC value = 55mV)), and 10 parts by mass of silane coupling agent (KBM-403, Shin-Etsu Chemical Co., Ltd. (residual DC value = 431mV)) were mixed. Then, they were fully mixed with a three-roller to form a uniform liquid to obtain a sealant.
[0141] [Comparative Example 2]
[0142] 600 parts by weight of the photocurable compound 1, 80 parts by weight of a (meth) acrylic compound (2CL, manufactured by Shin-Nakamura Chemical Co., Ltd. (residual DC value = 73 mV)), 50 parts by weight of a thermosetting agent (adipic acid dihydrazide, manufactured by Otsuka Chemical Co., Ltd. (residual DC value = 53 mV)), 20 parts by weight of a photopolymerization initiator (OXE-01, manufactured by BASF Japan Co., Ltd. (residual DC value = 68 mV)), 150 parts by weight of inorganic particles (silica particles: S-100, manufactured by Nippon Shokubai Chemical Co., Ltd. (residual DC value = 51 mV)), 90 parts by weight of organic particles (fine particle polymer F351, manufactured by Aica Kogyo Co., Ltd. (residual DC value = 55 mV)), and 10 parts by weight of a silane coupling agent (KBM-403, manufactured by Shin-Etsu Chemical Co., Ltd. (residual DC value = 431 mV)) were mixed. Then, these were fully mixed by a three-roller to form a uniform liquid to obtain a sealant.
[0143] [Comparative Example 3]
[0144] 400 parts by mass of the photocurable compound 2, 100 parts by mass of an epoxy compound (EP-4010S, manufactured by ADEKA, bisphenol A type (residual DC value = 64 mV)), 50 parts by mass of an epoxy compound (Epogosey NPG, manufactured by Yokkaichi Kogyo Co., Ltd., 1,4-butanediol diglycidyl ether (residual DC value = 300 mV)), 50 parts by mass of a (meth)acrylic compound (Ebecryl 3700, Daicel Cytec (residual DC value = 52mV)), 80 parts by weight of (meth) acrylic compound (2CL, Shin-Nakamura Chemical Co., Ltd. (residual DC value = 73mV)), 50 parts by weight of thermosetting agent (adipic acid dihydrazide, Otsuka Chemical Co., Ltd. (residual DC value = 53mV)), 20 parts by weight of photopolymerization initiator (OXE-01, BASF (residual DC value = 68mV)), 150 parts by weight of inorganic particles (silica particles: S-100, Nippon Shokubai Chemical Co., Ltd. (residual DC value = 51mV)), 90 parts by weight of organic particles (fine particle polymer F351, Aica Kogyo Co., Ltd. (residual DC value = 55mV)), and 10 parts by weight of silane coupling agent (KBM-403, Shin-Etsu Chemical Co., Ltd. (residual DC value = 431mV)) were mixed. Then, these were fully mixed by three rolls to form a uniform liquid to obtain a sealant.
[0145] [Comparative Example 4]
[0146] 200 parts by mass of the photocurable compound 1, 40 parts by mass of an epoxy compound (EP-4010S, manufactured by ADEKA, bisphenol A type (residual DC value = 64 mV), 200 parts by mass of an epoxy compound (850-S, manufactured by DIC, bisphenol A type (residual DC value = 133 mV), 130 parts by mass of a (meth) acrylic compound (Ebecryl 3700, Daicel Cytec (residual DC value = 52mV)), 100 parts by weight of a (meth) acrylic compound (2CL, Shin-Nakamura Chemical Co., Ltd. (residual DC value = 73mV)), 50 parts by weight of a thermosetting agent (adipic acid dihydrazide, Otsuka Chemical Co., Ltd. (residual DC value = 53mV)), 20 parts by weight of a photopolymerization initiator (OXE-01, BASF (residual DC value = 68mV)), 150 parts by weight of inorganic particles (silica particles: S-100, Nippon Shokubai Chemical Co., Ltd. (residual DC value = 51mV)), 90 parts by weight of organic particles (fine particle polymer F351, Aica Kogyo Co., Ltd. (residual DC value = 55mV)), and 20 parts by weight of a silane coupling agent (KBM-403, Shin-Etsu Chemical Co., Ltd. (residual DC value = 431mV)) were mixed. Then, these were fully mixed by a three-roller to form a uniform liquid to obtain a sealant.
[0147] [Comparative Example 5]
[0148] 340 parts by weight of the photocurable compound 1, 130 parts by weight of an epoxy compound (EP-4010S, manufactured by ADEKA, bisphenol A type (residual DC value = 64 mV), 200 parts by weight of an epoxy compound (850-S, manufactured by DIC, bisphenol A type (residual DC value = 133 mV), 50 parts by weight of a thermosetting agent (adipic acid dihydrazide, manufactured by Otsuka Chemical Co., Ltd. (residual DC value = 53 mV)), 20 parts by weight of a photopolymerization initiator (OXE-01, manufactured by BASF (residual DC value = 68 mV)), 150 parts by weight of inorganic particles (silica particles: S-100, manufactured by Nippon Shokubai Chemical Co., Ltd. (residual DC value = 51 mV)), 90 parts by weight of an organic particle (fine particle polymer F351, manufactured by Aica Kogyo Chemical Co., Ltd.) Co., Ltd. (residual DC value = 55 mV)), and 20 parts by mass of a silane coupling agent (KBM-403, Shin-Etsu Chemical Co., Ltd. (residual DC value = 431 mV)) were mixed. Then, these were fully mixed with a three-roller to form a uniform liquid, thereby obtaining a sealant.
[0149] [evaluate]
[0150] The following evaluations were performed on the sealing agents obtained in Examples and Comparative Examples.
[0151] <Measurement of residual DC value of sealant and liquid crystal>
[0152] The above-mentioned sealant is mixed with liquid crystal, and the residual DC value is measured. 0.1g of liquid crystal sealant and 1g of liquid crystal (MLC-7026, manufactured by Merck) are put into a small bottle, heated at 120°C for 1 hour, and a liquid crystal mixture is obtained. Next, the liquid crystal mixture is taken out and injected into a glass unit (KSSZ-10 / B111M1NSS05, manufactured by EHC) in which an orientation film and a transparent electrode are pre-formed. A voltage of 5V is applied to the obtained unit for 1 second, and after a short circuit for 0.1 seconds, the voltage (residual DC value) remaining after 30 seconds is measured using a 6254 type measuring device (manufactured by Toyo Technica). It should be noted that for the case of only liquid crystal, the residual DC value is also measured in the same way. As a result, the residual DC value of only liquid crystal is 50mV.
[0153] <Determination of residual DC value of raw materials>
[0154] The above raw materials were mixed with liquid crystal, and the residual DC value was measured. 0.1 g of the compound and 1 g of liquid crystal (MLC-7026, manufactured by Merck) were placed in a vial and heated at 120°C for 1 hour to obtain a liquid crystal mixture. Next, the liquid crystal mixture was taken out and injected into a glass unit (KSSZ-10 / B111M1NSS05, manufactured by EHC) on which an orientation film and a transparent electrode were pre-formed. A voltage of 5 V was applied to the obtained unit for 1 second, and after a short circuit for 0.1 second, the voltage remaining after 30 seconds (residual DC value) was measured using a 6254 type measuring device.
[0155] <Afterimage Evaluation>
[0156] The sealant was applied using a dispenser (Shotmaster: manufactured by Musashi Engineering) onto a 40 mm × 45 mm glass substrate (RT-DM88-PIN, manufactured by EHC) on which a transparent electrode and an alignment film were previously formed. Specifically, a 35 mm × 40 mm square seal pattern (cross-sectional area 3500 μm 2 )(main seal); and the same sealing pattern (a 38mm×43mm quadrilateral sealing pattern) located on its outer periphery.
[0157] Next, a dispenser was used to precisely drop a liquid crystal (MLC-7026-000, manufactured by Merck) in an amount equivalent to the amount of liquid crystal in the laminated panel into the main seal frame. Next, the paired glass substrates were laminated under reduced pressure and then exposed to the atmosphere. The laminated two glass substrates were then kept in a light-shielding box for 3 minutes and irradiated with 100 mJ / cm2 The substrate was irradiated with light having a wavelength of 370 to 450 nm and heated at 120° C. for 1 hour. Polarizing plates were attached to both surfaces of the obtained substrate to prepare an evaluation substrate.
[0158] The electrodes were connected in such a way that only half of the surface of the evaluation substrate filled with liquid crystal was driven, and a voltage of 10V was applied while power was turned on at 65°C for 24 hours. Thereafter, the entire surface was driven at 4V, and the boundary line between half-surface drive and entire-surface drive was observed under a microscope. The evaluation of the afterimage was evaluated as follows based on the state on the boundary line of the substrate. In the case of narrowing the frame, it can be said that only ○ is a range that has no practical problems.
[0159] ○: No difference or afterimage is seen on the boundary line of the substrate
[0160] △: Afterimage is seen on the substrate boundary line within 1 mm from the end of the sealant
[0161] ×: Afterimage is seen on the substrate boundary line at a distance of 1 mm or more from the end of the sealing material
[0162] <Adhesion strength evaluation>
[0163] Using a screen plate, print the sealant on 25mm×45mm×1mm thick alkali-free glass. Make the seal pattern a circle with a diameter of 1mm. Then, place the paired alkali-free glass on the seal pattern and fix it with a clamp. For this test piece, use an ultraviolet irradiation device (made by Ushio Electric Co., Ltd.) to irradiate 500mW / cm 2 The UV light is used to cure the sealant. At this time, the illumination energy of the UV light is 3.0 J / cm 2 The test piece obtained by curing the sealant with light was heat-treated at 120° C. for 60 minutes in an oven to prepare a sample for measuring the adhesive strength.
[0164] For this sample, a tensile tester (manufactured by INTESCO) was used at a tensile speed of 2 mm / min, and the cured sealant was peeled off in a direction parallel to the bottom surface of the glass, thereby measuring the tensile strength of the plane. Here, the bonding strength is evaluated as follows based on the magnitude of the tensile strength of the plane. In the case of narrowing the frame, △ or above is preferred.
[0165] ○: Tensile strength is 15MPa or more
[0166] △: Tensile strength is 10 MPa or more and less than 15 MPa
[0167] ×: Tensile strength is less than 10 MPa
[0168] [Table 1]
[0169]
[0170] As shown in Table 1, for a sealant containing an epoxy compound, a compound containing a (meth) acrylic group·epoxy group, a (meth) acrylic compound, a thermosetting agent, and a photopolymerization initiator, and the content of the epoxy compound is 22 to 38% by mass, and the residual DC value of the mixture of the sealant and the liquid crystal is 200% or less relative to the residual DC value of the liquid crystal alone, the afterimage evaluation is good, and the bonding strength evaluation is also good (Examples 1 to 7). It is believed that sufficient adhesion is obtained by using a specified amount of epoxy compound. In addition, for a sealant with a low residual DC value when mixed with a liquid crystal, it can be said that the components in the sealant are not easily dissolved into the liquid crystal.
[0171] On the other hand, when the amount of the epoxy compound is less than 22% by mass, the result of the afterimage evaluation is good, but the result of the adhesion test is low (Comparative Example 2). On the other hand, when the amount of the epoxy compound exceeds 38% by mass, although the adhesion is good, the value of the afterimage residual DC tends to increase, and the afterimage evaluation is poor (Comparative Example 5).
[0172] Even when the content of the epoxy compound was 22 to 38% by mass, when the residual DC value when the sealing agent and the liquid crystal were mixed was high, the afterimage evaluation was poor in all cases (Comparative Examples 1, 3, and 4).
[0173] This application claims priority based on Japanese Patent Application No. 2020-034974 filed on March 2, 2020. The contents described in the specification of that application are incorporated herein in their entirety.
[0174] Industrial Applicability
[0175] According to the sealant of the present invention, a sealing member having high adhesion to a substrate can be obtained. In addition, the sealant is not easy to contaminate liquid crystal. Therefore, the sealant is very useful as a sealant for making a sealing member of various liquid crystal display panels.
Claims
1. A sealant for a liquid crystal dropping process, comprising: Epoxy compounds having no polymerizable functional groups other than epoxy groups, A (meth)acrylic group-epoxy group-containing compound having both a (meth)acrylic group and an epoxy group in one molecule, (Meth) acrylic compounds not having an epoxy group, Thermal curing agent, and Photopolymerization initiator, The content of the epoxy compound is 22 to 38% by mass. A mixture prepared by mixing the sealing agent for the liquid crystal dropping process and the liquid crystal MLC-7026 manufactured by Merck in a mass ratio of 1:10 was heated at 120°C in a vial for 1 hour, the mixture was placed in a glass unit having an orientation film and a transparent electrode, a voltage of 5V was applied for 1 second and a short circuit was performed for 0.1 second, and a residual DC value was measured 30 seconds later using a 6254 type measuring device manufactured by Toyo Technica, with respect to a residual DC value measured 30 seconds later using a 6254 type measuring device manufactured by Toyo Technica, after only the liquid crystal was heated at 120°C in a vial for 1 hour, only the liquid crystal was placed in the glass unit, a voltage of 5V was applied for 1 second and a short circuit was performed for 0.1 second, and a residual DC value was measured 30 seconds later using a 6254 type measuring device manufactured by Toyo Technica.
2. The sealing agent for liquid crystal dropping process according to claim 1, wherein Each component contained in the sealing agent for the liquid crystal dropping process was mixed with liquid crystal MLC-7026 manufactured by Merck at a mass ratio of 1:10, and heated in a vial at 120°C for 1 hour, and then placed in a glass cell having an alignment film and a transparent electrode, and a voltage of 5V was applied for 1 second and short-circuited for 0.1 second, and then the residual DC value was measured after 30 seconds using a 6254 type measuring device manufactured by Toyo Technica. The residual DC value of the component of 98% by mass or more of the sealing agent for the liquid crystal dropping process is 300% or less relative to the residual DC value measured after only the liquid crystal MLC-7026 manufactured by Merck was heated at 120°C in a vial for 1 hour, placed in a glass cell having an orientation film and a transparent electrode, and a voltage of 5V was applied for 1 second and short-circuited for 0.1 second, and then measured using a 6254 type measuring device manufactured by Toyo Technica for 30 seconds.
3. The sealing agent for a liquid crystal dropping process according to claim 1 or 2, wherein The proportion of the component having a molecular weight of 500 or more in the epoxy compound is 25% by mass or more.
4. The sealing agent for a liquid crystal dropping process according to claim 1 or 2, wherein The thermal curing agent is one or more selected from the group consisting of organic acid dihydrazide-based thermal latent curing agents, imidazole-based thermal latent curing agents, amine adduct-based thermal latent curing agents, and polyamine-based thermal latent curing agents. The sealing agent for a liquid crystal dropping method according to claim 1 or 2, further comprising inorganic particles. The sealing agent for a liquid crystal dropping process according to claim 1 or 2, further comprising organic particles. 7 . The sealing agent for a liquid crystal dropping process according to claim 1 , further comprising a silane coupling agent.
8. A method for manufacturing a liquid crystal display panel, comprising: A step of applying the sealing agent for a liquid crystal dropping process according to any one of claims 1 to 7 on one of a pair of substrates to form a seal pattern; A step of dropping liquid crystal into the region of the seal pattern of the one substrate or onto the other substrate while the seal pattern is not cured; a step of superimposing the one substrate and the other substrate via the seal pattern; and A step of curing the seal pattern.
9. The method for manufacturing a liquid crystal display panel according to claim 8, wherein: In the step of curing the seal pattern, light is irradiated onto the seal pattern.
10. The method for manufacturing a liquid crystal display panel according to claim 9, wherein: In the step of curing the seal pattern, heating is performed after irradiation with light.
Citation Information
Patent Citations
Curable resin composition for liquid crystal display element, sealing material for one drop fill technology, vertically conducting material, and liquid crystal display element
JP2006023583A
Low-elusion epoxy resin and partially esterified epoxy resin of the same, production method of the same, and curable resin composition comprising the same
JP2015028184A
Image generation device, image generation and display system, and image generation method
JP2020034974A
Sealing material for liquid crystals and process for production of liquid crystal panels with the same
CN101313244A
Sealant for liquid crystal dropping method
CN102640040A